Етичні парадигими в бізнесі та суспільстві - Drobnic, Janez; Toros, Jani; Weis, Lidija (Dr. Viktor Koval, 2020)
Introduction. Ethical conduct emerges as a topic of discussion especially when conflicts arise between people, which cannot be resolved by regulation because of new circumstances and situations, or when legal norms prove insufficient or are disregarded, therefore leading to ethically unacceptable practices. Ethical issues of this kind are now at the forefront of social treatment, mainly because modern management practices have become increasingly problematic, areas of activity are expanding, and businesses and other forms of activity are increasingly under ethical pressures from multiple stakeholders. According, ethical behaviour is becoming a global issue and a pressing topic both in general and professional discussions; scientific analysis is therefore extremely relevant. Aim and tasks. This article’s aim is to study the ethical principles and morally ethical problems that arise in various business environments, such as medical, technical, legal, and commercial, as well as in sectors, including state, non-governmental, and private markets. It also explores ethical bases change over time and depending on social flows. Undoubtedly, stakeholders are interested in such ethics-based governance, which means that ethical issues should be effectively put into practice. The study identifies the key paradigms of how different sectors operate and what issues arise. Results. The diachronic study finds that there was almost no interest in studying business ethics over the last century. The beginning of the 21st century saw strong increase in interest regarding these issues, as evidenced by the number of studies and analyses, the introduction of ethical business courses, and other ethical issues. Hyperconnected modern society is increasingly globally interdependent, wherefore interest in the appropriate culture and ethics of action is increasing with the aim of reducing risks and conflicts. Nongovernmental organizations increasingly involved in these processes, develop their business practices of responsibility and care for vulnerable groups and the environment. They have indirectly become a strong factor in leveraging for the ethical conduct of free market operators as well as state/public institutions. Conclusions. The existing studies identified seven key ethical paradigms that emerge in the operation of non-governmental, state, and market sectors, differing in key two dimensions: the first extends from emphasizing community (communitarianism) to exposing individuality, and the second from self-orientation (egocentricity) to a focus on the other (sociocentricity). On this basis, an array of various approaches to ethics can emerge, providing for useful tools for the professional analysis of business practices, as well as to assist stakeholders in introducing better business at all levels.